Synthesis of functionalized β-lactams and pyrrolidine-2,5-diones through a metal-free sequential Ugi-4CR/cyclization reaction - Ghabraie, Elmira; Balalaie, Saeed; Mehrparvar, Saber; Rominger, Frank (The journal of organic chemistry, 2014)
An efficient approach for the synthesis of functionalized β-lactams and pyrrolidine-2,5-diones was achieved through a sequential Ugi-4CR/cyclization reaction. Diversity-oriented synthesis, good to high yields, easy workup, and short reaction times are advantages of this procedure.
Gesehen am 03.09.2020